2001
DOI: 10.1007/pl00002943
|View full text |Cite
|
Sign up to set email alerts
|

Vascular disease in younger-onset diabetes: comparison of European, Asian and American Indian cohorts of the WHO multinational study of vascular disease in diabetes

Abstract: (MSVDD) has been described in previous papers [1±3]. Of the original 4729 diabetic patients who underwent baseline examination at the ten centres, 994 (21 %) had diabetes diagnosed before the age of 30 years. Previous analysis showed that patients with younger-onset diabetes were more likely to develop vascular diseases than those with diabetes diagnosed after the age of 30 [4,5]. It has also been shown that there was a large variation in incidence of vascular disease between centres [1]. The purpose of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
(11 reference statements)
0
18
0
Order By: Relevance
“…Fifty-seven studies published from 1990 to 2008 met the inclusion criteria: 13 European studies on AMD (4 multicentre studies [13,[22][23][24] , 6 prevalence studies from the Netherlands [25] , Germany [26] , France [27] , the UK [28] , the European North of Russia [29] and Bulgaria [2] , and 3 incidence studies from Rotterdam [22,30] and Germany [31] ), 23 studies of diabetic retinopathy (1 global [32] , 3 European [33][34][35] ; 2 multicentre European [15,36,37] and 2 multicentre from Spain [38] and Germany [26,39] , 1 long-term follow-up study from Germany [40] ; 7 population-based studies [2,30,31,[41][42][43][44][45] , 5 cross-sectional studies from Germany [39] , France [46] , Europe [27,37] , Spain [47] and 2 literature reviews [16,35] ), 5 studies of ocular hypertension, including 4 cross-sectional studies: 1 from Spain [48] , 2 from France [49,50] , 1 cross-sectional study of high intraocular pressure ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-seven studies published from 1990 to 2008 met the inclusion criteria: 13 European studies on AMD (4 multicentre studies [13,[22][23][24] , 6 prevalence studies from the Netherlands [25] , Germany [26] , France [27] , the UK [28] , the European North of Russia [29] and Bulgaria [2] , and 3 incidence studies from Rotterdam [22,30] and Germany [31] ), 23 studies of diabetic retinopathy (1 global [32] , 3 European [33][34][35] ; 2 multicentre European [15,36,37] and 2 multicentre from Spain [38] and Germany [26,39] , 1 long-term follow-up study from Germany [40] ; 7 population-based studies [2,30,31,[41][42][43][44][45] , 5 cross-sectional studies from Germany [39] , France [46] , Europe [27,37] , Spain [47] and 2 literature reviews [16,35] ), 5 studies of ocular hypertension, including 4 cross-sectional studies: 1 from Spain [48] , 2 from France [49,50] , 1 cross-sectional study of high intraocular pressure ...…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, existing studies focus for the most part only on a single eye disorder, such as AMD [12][13][14] , diabetic retinopathy [15][16][17] , glaucoma [18,19] or cataract [20,21] . Despite the high value of the data from these studies, there is still a pressing need for a complete picture of the epidemiological status of age-related eye diseases in Europe.…”
mentioning
confidence: 99%
“…These include age, glycemic control, smoking, hypertension, and male sex (5,6,9,10,14,18). Participants were considered hypertensive if they had a systolic blood pressure Ն140 mmHg, a diastolic blood pressure Ն90 mmHg, or if they were taking antihypertension medication.…”
Section: Measurement Of Baseline Risk Factorsmentioning
confidence: 99%
“…Work restrictions are common, and most individuals with LEA require extensive life-long health services. Lowerextremity amputations occur with significantly greater frequency in diabetic American Indians than in diabetic people of other ethnicities (5,6).…”
mentioning
confidence: 96%
“…Previous studies have shown that hyperglycemia (5,6,9,10), duration of diabetes (5,6), male sex (2,5,6,10), and prevalent microvascular disease (5,6,10) contribute to LEA risk in American Indians.…”
mentioning
confidence: 99%